2019
DOI: 10.11648/j.ajbls.20190704.11
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Exogenous Peptide Effect on the TGF-β1 Expression – A Risk Factor for the Hepatocellular Carcinoma Recurrence

Abstract: An article deals with the influence of the transforming growth factor beta-1 (TGF-β1) on the carcinogenesis of hepatic cells, as well as attention is given to the role of this factor in the hepatocellular carcinoma (HCC) progression. We monitored two groups of patients: in the treatment group, patients were administered cancer vaccine therapy and anti-relapse immune corrector Arecur®-a complex of exogenous peptides with anti-inflammatory, anti-infective and regenerating properties; in the reference group, pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Studies have shown that contact of immune peptides with mucosal cells significantly increases the expression of secretory immunoglobulin A. [25] The ability of immune proteins to stimulate macrophage migration and induce apoptosis of atypical cells opens new possibilities for the use of antirelapse immunocorrection [26] Encouraging clinical results of the use of immune proteins for the prevention of cancer recurrence were obtained [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that contact of immune peptides with mucosal cells significantly increases the expression of secretory immunoglobulin A. [25] The ability of immune proteins to stimulate macrophage migration and induce apoptosis of atypical cells opens new possibilities for the use of antirelapse immunocorrection [26] Encouraging clinical results of the use of immune proteins for the prevention of cancer recurrence were obtained [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the most interesting is the nonspecific mechanism of activation by immune proteins of immunocompetent cells. Due to the effect of tissue accumulation, immune peptides attach to cell membranes in the target organ and thus provoke their more productive interactions with T-lymphocytes, NK-cells and macrophages [33,34,37]. On the one hand, interacting with the ectopically located endometrial tissue, RJP-1 reduces perifocal inflammation, on the other hand, defensins stimulate the synthesis of TNF-α by macrophages.…”
Section: Figure 1 Immunolocalization Of Cd26 In the Eutopic (A-c) Anmentioning
confidence: 99%